Evaluation of superfluid helium cooling schemes and application for HL-LHC recombination dipole D2. (October 2018) - Rousset, B.; Millet, F.
Highlights: HeII offers peculiar heat transport properties used in superconducting devices. Different HeII cooling architectures have been reviewed for distributed heat loads. Calculations are applied to cool the D2 magnet of the HL-LHC project at CERN. Abstract: Superfluid helium cooling offers the possibility to improve the performances of superconducting devices and infrared detectors with lower operating temperatures and provides extremely high heat transfer performances. In this paper, various cooling architectures are studied and the amplitude and the space distribution of the heat loads are taken into account. Complete and simplified analytical models are proposed using either the He II heat transport or convection. These cooling options could be evaluated to pre-design the future generation of superconducting devices required in laboratory test beds and the large scale research infrastructures such as particle accelerators and thermonuclear fusion reactors. As an example, the different schemes proposed are calculated for the recombination dipole D2 of the High Luminosity Large Hadron Collider Project at CERN (HL-LHC). Finally a comparison analysis is provided for this specific case study.